PENGEMBANGAN BUKU AJAR DRAMA BERBASIS KESENIAN LOKAL - Dwi Rohman Soleh; Muhamad Binur Huda (Widyabastra : Jurnal Ilmiah Pembelajaran Bahasa dan Sastra Indonesia, 2013)
The purposes of this research are:  (1) to describe the recent learning of drama in LPTK, which includes describing the application of existing drama textbooks; ( b ) describing  the lecturers’ and students’ necessity associated with the  improvement of drama textbooks in LPTK. (2) to describe the development of drama textbooks which based on local arts -, which includes : (a ) describing  the development of a prototype ( draft ) into the drama textbook -based on local arts by expert judgment , (b )to  describe the development and improvement of the drama textbooks based on local arts –regarded  to limited testing in the research field. (3) to describe the effective level of drama textbooks based on the local arts than conventional textbooks in LPTK. (4) to describe the dissemination of drama textbook –based the local arts. The research and development stages which are stated by Borg and Gall (1983:775) include product development, product testing in the field, and correction of products based on the data obtained after the products are tested in the research field. The outcomes of this research are: ( 1 ) learning devices including: syllabus , SAP , ( 2 ) drama textbooks based on local arts.Keywords : drama textbook, local arts